Smart City di Indonesia : Analisis Bibliometrik - Selvia Junita Praja; Serly Wulandari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Smart cities are trending as an innovative approach to address urban problems. This study aims to analyse the trend of research publications on smart cities in Indonesia with a bibliometric analysis approach. The articles used in this study were obtained from Scopus data. From 131 articles found in the scopus database between 2013 and 2024. The selected articles were then managed using biblioshiny and Vosviewer software. The results showed that publications related to smart cities experienced fluctuations from the last 10 years. The article with the most citations is entitled Strengthening waste recycling industry in Malang (Indonesia): Lessons from waste management in the era of Industry 4.0 has the most citations of 85 citations. While seen from the highest affiliation shows that Gadjah Mada University is an institution with a total of 70 publications. Mapping articles based on the relationship between keywords (co-occurance) is formed into 12 clusters, each cluster describes topics that are often discussed in smart city-related literature, such as urban planning, social networking, e-government, public services, urban development, sustainable development, internet of things (IoT), urban growth, economic, artificial intelligence, and secondary datum.